ANGULAR STRUCTURE OF FRII RADIO SOURCES 3C169.1 AND 3C263 AT DECAMETER WAVELENGTHS - Vashchishin, R. V.; Shepelev, V. A.; Lozinskyy, A. B.; Lytvynenko, O. A. (Одеські астрономічні публікації, 2016)
The radio galaxy 3C169.1 and the quasar 3C263, located at nearly the same distance with red shift z>0.6, have similar morphological and spectral characteristics. The maps of the sources obtained at decimeter and centimeter wavelengths have shown they are FRII radio sources with steep spectra and approximately equal angular sizes. The very first investigation of the sources structure at decameter wavelengths is presented in the report. Observations were made using a network of the URAN decameter interferometers with baselines 42 to950 km and with maximum angular resolution of arcsec order of magnitude. The models of the image of these sources based on visibility functions measured have been obtained at frequencies of 20 and 25 MHz. They were composed of elliptical components with Gaussian brightness distribution. To facilitate the comparison of these lowfrequency models with high-frequency radio images, the latter were converted to the similar models by fitting the Gaussian components to lobes and hot spots selected at the maps. Comparison of the models revealed changes in a structure of the sources caused by the frequency decrease.